2020
DOI: 10.3390/microorganisms8070996
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Functional Annotations of Important Genes in the AHPND-Causing pVA1 Plasmid

Abstract: Acute hepatopancreatic necrosis disease (AHPND) is a lethal shrimp disease. The pathogenic agent of this disease is a special Vibrio parahaemolyticus strain that contains a pVA1 plasmid. The protein products of two toxin genes in pVA1, pirAvp and pirBvp, targeted the shrimp’s hepatopancreatic cells and were identified as the major virulence factors. However, in addition to pirAvp and pirBvp, pVA1 also contains about ~90 other open-reading frames (ORFs), which may encode functional proteins. NCBI BLASTp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Most studies have revealed that the AHPND causing bacteria usually release their toxins after invading the digestive tract, which results in the production of the characteristic symptoms [ 14 , 17 , 40 ]. Although the details of the molecular mechanisms involved in the pathogenesis of AHPND are still unknown, it is believed that PirA and PirB form a heterodimer that binds to receptors, after which PirB enters the cell through pore formation and then circulates to the hepatopancreas where it exerts cellular damage including sloughing of epithelial cells into the lumen (see recent reviews by [ 41 , 42 ]). Thus, damage to the hepatopancreatic tubules allows PirB toxin to be released into the intertubular space, which is then carried into hemolymph to infect hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have revealed that the AHPND causing bacteria usually release their toxins after invading the digestive tract, which results in the production of the characteristic symptoms [ 14 , 17 , 40 ]. Although the details of the molecular mechanisms involved in the pathogenesis of AHPND are still unknown, it is believed that PirA and PirB form a heterodimer that binds to receptors, after which PirB enters the cell through pore formation and then circulates to the hepatopancreas where it exerts cellular damage including sloughing of epithelial cells into the lumen (see recent reviews by [ 41 , 42 ]). Thus, damage to the hepatopancreatic tubules allows PirB toxin to be released into the intertubular space, which is then carried into hemolymph to infect hemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Transposases are enzymes that are involved in the translocation of DNA transposons to another location in the plasmid and/or genome (Harmer et al 2020). In fact, more than one transposase gene can be found in a single plasmid, likely due to the heteromeric structure of some of these enzymes (Peters et al 2014;Wang et al 2020).…”
Section: R a F Tmentioning
confidence: 99%
“…The PirA vp and PirB vp genes are part of the same operon ( 18 ). The genes are synchronously regulated and expressed ( 19 ). However, how VP AHPND colonizes the stomach, hepatopancreas, and intestinal tract, and how the PirA vp and PirB vp toxins interact with these tissues are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Structural analyses have revealed the functional relationship between PirA vp /PirB vp and the Cry toxin of Bacillus thuringiensis ( 19 ). The Cry pore-forming toxin includes three functional domains: N-terminal pore-forming domain I, middle receptor binding domain II, and C-terminal sugar/receptor binding domain III ( 19 ). The toxic mechanism of Cry toxins involves the recognition of n-acetylgalactosamine, which is present on several receptors, by domain III.…”
Section: Introductionmentioning
confidence: 99%